Using single visits into integrated occupancy models to make the most of existing monitoring programs. Issue 12 (28th September 2021) - Lauret, Valentin; Labach, Hélène; Authier, Matthieu; Gimenez, Olivier
Abstract: A major challenge in statistical ecology consists of integrating knowledge from different data sets to produce robust ecological indicators. To estimate species distribution, occupancy models are a flexible framework that can accommodate several data sets obtained from different sampling methods. However, repeating visits at sampling sites is a prerequisite for using standard occupancy models. Occupancy models were recently developed to analyze detection/non‐detection data collected during a single visit. To date, single‐visit occupancy models have never been used to integrate several different data sets. Here, we showcase an approach that combines two data sets into an integrated single‐visit occupancy model. As a case study, we estimated the distribution of common bottlenose dolphin ( Tursiops truncatus ) over the northwestern Mediterranean Sea by combining 24, 624 km of aerial surveys and 21, 464 km of at‐sea monitoring. We compared the outputs of single‐ vs. repeated‐visit occupancy models into integrated occupancy models. Integrated models allowed a better sampling coverage of the targeted population, which provided a better precision for occupancy estimates than occupancy models using data sets in isolation. Overall, single‐ and repeated‐visit integrated occupancy models produced similar inference about the distribution of bottlenose dolphins. We suggest that single‐visit occupancy models open promising perspectives for the use of existing ecological data sets.